Resilience applications to social isolation and loneliness in older adults: a scoping review to develop a model and research agenda - Wister, Andrew; Kim, Boah; Levasseur, Mélanie; Poulin, Valérie; Qiu, Sarah; Yuwono, Esther; Meynet, Stéphanie; Beadle, Julie; Kadowaki, Laura; Klasa, Katarzyna; Linkov, Igor (Frontiers in Public Health, 2025)
BackgroundThe development of a theoretical model applied to social isolation and loneliness (SI/L) among older adults has not kept pace with the exponential growth in empirical research, especially since the COVID-19 pandemic. One promising but under-investigated area is the contribution of resilience models to this field. This paper provides a scoping review of the application of resilience theoretical models to social isolation and loneliness and suggests directions for the development of an integrated new model.MethodUsing the Arksey and O’Malley scoping review method, searches of four databases with 13 keywords were conducted April 9, 2024, with 17 articles meeting the inclusion criteria of the 1,671 extracted articles.ResultsFindings were summarized using thematic analysis separated into four major themes: (1) coping self-efficacy to reduce SI/L; (2) moderating expectations to foster resilience to SI/L; (3) the effects of social support, the environment and resilience on COVID-19 stressors, and; (4) resilience as a mediator between SI/L and mental health. We integrate these findings into a new model entitled the Resilience and Social Isolation Model of Aging (RSIMA).ConclusionRSIMA highlights SI/L as a dynamic process on a continuum, as well as elucidating what broader factors can lead to improved social connection, contributing to both individual-level and community resilience. To address the looming public health crisis of social isolation and loneliness among older people, future research studies must consider a systems-level perspective to SI/L and resilience.